2009
DOI: 10.1186/1471-2474-10-102
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the Dutch translation of the VISA-P questionnaire for patellar tendinopathy

Abstract: Background: The VISA-P questionnaire evaluates severity of symptoms, knee function and ability to play sports in athletes with patellar tendinopathy. This English-language self-administered brief patient outcome score was developed in Australia to monitor rehabilitation and to evaluate outcome of clinical studies. Aim of this study was to translate the questionnaire into Dutch and to study the reliability and validity of the Dutch version of the VISA-P.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

18
99
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(121 citation statements)
references
References 13 publications
18
99
2
Order By: Relevance
“…This adaptation showed good psychometric properties in Spanish athletes, and that the scores of the groups were very similar to those obtained from subjects using other versions 12,28,29,37,39 of the same scale supports our findings.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…This adaptation showed good psychometric properties in Spanish athletes, and that the scores of the groups were very similar to those obtained from subjects using other versions 12,28,29,37,39 of the same scale supports our findings.…”
Section: Discussionsupporting
confidence: 80%
“…As the authors suggested in the original publication, the VISA-P should not be considered a diagnostic tool, because there were no significant differences between the scores of athletes with tendinopathy and those of patients with other knee injuries. 12,28,29,39 In the study of VISA-P-Sp correlation with SF-36 components, participants with higher levels of symptoms had, as expected, a poorer quality of life related to health. This finding helps to confirm the external validity of the questionnaire and its adaptation.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, the original version of the VISA-P was not assessed in terms of internal consistency, but validations of this questionnaire in other languages had high Cronbach alpha values. 7,14,25 This acceptable internal consistency across different cultures may be an indication that the original VISA-P is well formulated and also has good internal consistency. The German version (Cronbach α = .88) 14 and the Swedish version (Cronbach α = .83) 7 had higher internal consistency than the Brazilian version; however, they are all well within the range considered acceptable.…”
Section: Discussionmentioning
confidence: 99%